2024
DOI: 10.3390/cimb46040181
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Flavonoid Research: Sources, Biological Activities, and Developmental Prospectives

Baocheng Hao,
Zhen Yang,
Haoyu Liu
et al.

Abstract: At present, the occurrence of a large number of infectious and non-communicable diseases poses a serious threat to human health as well as to drug development for the treatment of these diseases. One of the most significant challenges is finding new drug candidates that are therapeutically effective and have few or no side effects. In this respect, the active compounds in medicinal plants, especially flavonoids, are potentially useful compounds with a wide range of pharmacological activities. They are naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 241 publications
0
2
0
Order By: Relevance
“…Yang et al identified about 102 compounds from the fruiting bodies of H. erinaceus , including organic acids, nucleotides and analogues, amino acids, carbohydrates and derivatives, flavonoids, unsaturated fatty acids, terpenoids, phenolic acids, phenylpropanoid, and steroids [ 29 ]. The authors further suggested that flavonoids which were qualitatively detected in the analysis (luteolin, apigenin, diosmetin, hispidulin, and acacetin) could function as active components in H. erinaceus based on previous studies which demonstrated flavonoids’ pharmacological functions which include neuroprotection, improved learning and memory, anti-inflammatory, and more [ 30 , 31 , 32 ]. Of note, in a study by He et al, two isoflavones were identified and isolated in H. erinaceus mycelium: genistein and daidzein, comprising 15% and 12% of the ethanolic extract, respectively [ 33 ].…”
Section: Identification Of Novel Bioactive Compounds In Her...mentioning
confidence: 99%
“…Yang et al identified about 102 compounds from the fruiting bodies of H. erinaceus , including organic acids, nucleotides and analogues, amino acids, carbohydrates and derivatives, flavonoids, unsaturated fatty acids, terpenoids, phenolic acids, phenylpropanoid, and steroids [ 29 ]. The authors further suggested that flavonoids which were qualitatively detected in the analysis (luteolin, apigenin, diosmetin, hispidulin, and acacetin) could function as active components in H. erinaceus based on previous studies which demonstrated flavonoids’ pharmacological functions which include neuroprotection, improved learning and memory, anti-inflammatory, and more [ 30 , 31 , 32 ]. Of note, in a study by He et al, two isoflavones were identified and isolated in H. erinaceus mycelium: genistein and daidzein, comprising 15% and 12% of the ethanolic extract, respectively [ 33 ].…”
Section: Identification Of Novel Bioactive Compounds In Her...mentioning
confidence: 99%
“…Plant families such as Lamiaceae, Rutaceae, Myrtaceae, Asteraceae, and Lauraceae are recognized for their abundant reservoirs of essential oils [45]. Similarly, families including Fabaceae, Rosaceae, Rutaceae, and Asteraceae are known for their richness in flavonoids [46].…”
Section: Introductionmentioning
confidence: 99%